Study of Desert Development Programme (1988-89) - Planning Commission (Planning Commission, 1993)
Desert Areas of the Country are one of the backward areas identified for special attention to be paid to their speedy development. These areas are faced with certain peculiar problems inhibiting the process of development. On account of difficult physiography, varying agro-climatic conditions and distinct sociocultural features, the desert areas have remained backward.
Programme Evaluation Organisation Planning Commission Government of India
Planning Commission Government of India